Landscapes of Resistance : Narratives around Sacred Places in Sinjar (Iraq) and the Islamic State's Genocide against Yezidis - Rassbach, Benjamin, (Iran and the Caucasus Monographs ;, 2025)
On August 3, 2014, the Sinjar region of Northern Iraq was attacked by the "Islamic State". Killing and abducting thousands, the jihadists also destroyed many of the religious minority's shrines. Others, however, were defended by local fighters and groups affiliated with the PKK. In the aftermath of the genocide, stories of divine intervention into the defence bolstered land claims of serveral Kurdish political groups. Through extensive fieldwork in the region, I trace imaginaries of Sinjar as a landscape of resistance and a communal history of continuous persecution to current political disputes and attempts to construct a unified Yezidi identity. See Less